The effect of autologous bone marrow-derived stem cells with estimation of molecular events on tooth socket healing in diabetic rabbits (Immunohistochemical study) - Mohamed, Mohamed A; Younis, Wasan H; Yaseen, Nahi Y (Journal of Baghdad College of Dentistry, 2013)
Background: Healing of a tooth extraction socket is a complex process involving tissue repair and regeneration. It involves chemotaxis of appropriate cells into the wound, Transformation of undifferentiated mesenchymal cells to osteoprogenitor cells, proliferation and differentiation of committed bone forming cells, extracellular matrix synthesis, mineralization of osteoid, maturation and remodeling of bone. These cellular events are precisely controlled and regulated by specific signaling molecules. Some of these like transforming growth factor beta (TGF-?), vascular endothelial growth factor (VEGF), bone morphogenetic proteins (BMP) and insulin like growth factors (IGF) are well conserved proteins involved in the initial response to injury and repair in soft and hard tissue. Materials and Methods: 48 rabbits weighting an average of (2.5 - 3 kg) were used in this experimental study, and divided into 3 groups as follows; group A ( contains 16 healthy rabbits regarded as control group ) , Group B ( contains 16 diabetic rabbits not received treatment ), group C ( contains 16 controlled diabetic rabbits received insulin as a treatment ), the lower incisor for each rabbits was extracted, after 2, 10, 20 and 30 days of healing periods after scarification , the socket was analysed by immunohistochemical (IHC) estimation of growth factors : TGFbeta-3 , VEGF , IGF-1R , BMP-4 . Results: IHC findings revealed high positive expression of TGFbeta-3, BMP-4 on fibroblasts, osteoproginetor cells, osteoblasts and osteocytes,high positive expression of VEGF on endothelial cells and high positive expression of IGF-1R on endothelial cells and moderate expression on osteoblasts. Conclusions: The inhibition of proliferation and migration of osteoblasts, or differentiation from progenitor cells, is implicated in the delay of teeth sockets healing. For this fact the results of the present study concluded that in the diabetic healing bone (rabbits of group B), the onset of cell proliferation and osteoblast differentiation were delayed and subsequently prolonged healing process when compared with the other groups (rabbits of group A,Cand D).